2004
DOI: 10.1172/jci200420096
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated LIGHT expression on T cells mediates intestinal inflammation and contributes to IgA nephropathy

Abstract: Whether and how T cells contribute to the pathogenesis of immunoglobulin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 38 publications
(31 reference statements)
2
40
0
Order By: Relevance
“…(b) Recombinant LIGHT can directly costimulate T cell responses (21). (c) Mice expressing the LIGHT transgene on the T cell lineage exhibited severe T cell-mediated inflammation and autoimmune diseases (9,11). (d) Blockade of LIGHT by HVEM-Ig reduced T cell proliferation and the incidences of T cell-mediated diseases (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) Recombinant LIGHT can directly costimulate T cell responses (21). (c) Mice expressing the LIGHT transgene on the T cell lineage exhibited severe T cell-mediated inflammation and autoimmune diseases (9,11). (d) Blockade of LIGHT by HVEM-Ig reduced T cell proliferation and the incidences of T cell-mediated diseases (11).…”
Section: Discussionmentioning
confidence: 99%
“…LIGHT is a potent T cell costimulatory molecule that appears to interact with the herpesvirus entry mediator (HVEM) expressed on T cells (5,6,8). Unlike most other costimulatory molecules delivering signals from APCs, the upregulation of LIGHT on T cells enhanced T cell-mediated immunity and promoted autoimmune diseases and inflammation (9)(10)(11). Local expression of LIGHT on tumor tissues induced a robust expansion and activation of T cells that led to the rejection of local and distal tumors (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we focused on 3 cytokines that have been implicated in epithelial barrier dysfunction, diarrhea, or intestinal inflammatory disease: IFN-g, TNF, and the TNF superfamily member LIGHT (lymphotoxin-like inducible protein that competes with glycoprotein D for herpesvirus entry mediator on T cells) (6)(7)(8)(9)(10)(11). However, the effects of these cytokines on intestinal physiology in vivo have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown in vitro that LIGHT induces apoptosis in several tumor cell lines, there are conflicting reports in regard to the specific receptor mediating this effect (9,10). Recent studies have suggested a potential role of LIGHT in inflammatory diseases including atherosclerosis (11), arthritis (12), IgA nephropathy (13), and inflammatory bowel disease (14). Despite these lines of investigation, the mechanism by which LIGHT mediates inflammatory responses remains elusive.…”
Section: Introductionmentioning
confidence: 99%